Targeting EGFR for Treatment of Glioblastoma: Molecular Basis to Overcome Resistance - Taylor, Tiffany E. (2012)
Glioblastoma (glioblastoma multiforme; GBM; WHO Grade IV) accounts for the majority of primary malignant brain tumors in adults. Amplification and mutation of the epidermal growth factor receptor (EGFR) gene represent signature genetic abnormalities encountered in GBM. A range of potential therapies that target EGFR or its mutant constitutively active form, ΔEGFR, including tyrosine kinase inhibitors (TKIs), monoclonal antibodies, vaccines, and RNA-based agents, are currently in development or in clinical trials for the treatment of GBM. Data from experimental studies evaluating these therapies have been very promising; however, their efficacy in the clinic has so far been limited by both upfront and acquired drug resistance. This review discusses the current status of anti-EGFR agents and the recurrent problem of resistance to these agents that strongly indicates that a multiple target approach will provide a more favorable future for these types of targeted therapies in GBM.